Heat Transfer and Magnetohydrodynamic Nanofluid Flow Caused by a Stretching Sheet Heated Convectively: Numerical Investigation (European Journal of Pure and Applied Mathematics, 2025)
This paper describes a new study that looks at how a magnetohydrodynamic (MHD) nanofluid moves and transfers heat over a porous medium with a stretched sheet that moves in a straight line. This study investigates the effects of heat radiation, viscous dissipation, and convective boundary conditions (CBCs) on the dynamics of nanofluids, an area that has received insuffi-cient exploration despite its significance in both commercial and scientific contexts. The research formulates the fundamental conservation equations for mass, momentum, heat, and nanoparticle concentration, which are transformed from nonlinear PDEs into a system of ODEs. These equations are solved numerically using the Hermite collocation method (HCM), with results visualized to illustrate the impact of key physical parameters. This work has practical applications in fields such as cooling technologies, energy systems, and materials engineering, where enhanced thermal management and precise control over nanofluid properties are crucial for performance optimization.
Keywords: Nanofluid; Convective boundary condition; Slip impacts; Thermal radiation; HCM.